Elizabethan Peterborough : the dean and chapter as lords of the city - Gifford, Daphne H.; Mellows, William Thomas (Publications of the Northamptonshire Record Society ;, 1956)
Transcripts, 1542-1604, of documents chiefly concerned with the powers and privileges of the dean and chapter, with their tenants and officers and their acts and decrees in chapter; together with court rolls of their manor court of Peterborough 1564-1599, an estreat roll of their court of common pleas, 1570-1580, and a calendar of surrenders of and admissions to property recorded in Peterborough court rolls, 1564-1599.